Impact of climate change on housing design the coping and adaptation strategies of residential communities in Davao City - Alvarez, Louis D. (2020)
Coping and adaptation strategies vary from region to region, depending on the presence of climate-related hazards in the area. Simple yet effective techniques could pioneer to the development and implementation of guidelines focusing on the impacts of hazards to a structure and its built environment. In the case of hazard-prone residential communities, it is alarming that these communities experience such hazards, regardless of frequency nor intensity. Davao City, like any other city in the world, suffers from the effects of climate change. Architecture is greatly influenced by climatic factors. The four identified study areas have their own history on climate-related hazards. These significant events display the vulnerability of the affected areas yet residents continue to reside in these places. The researcher dentified the climatic factors affecting the design and materials of houses, the frequency of the climate- related hazards in the area, as well as their applied coping and adaptation techniques. These are factors in determining the applicable design approaches to effectively reduce the effects of climate-related hazards in hazard-prone residential communities in Davao City. Through the development of thematic maps of hazard-prone areas in the city, the researcher was able to identify the areas of study. The assessment of existing house structures in terms of design and materials used had led to the identification of the physical structures of houses. Data on their climate hazard experience and applied coping and adaptation strategies was acquired through key informant interview of the residents. Inputs of professionals and persons of interest also played a huge role in the development of design strategies for adaptive housing design. The results of the study revealed the Vulnerability, Capacity, and Resilience of the identified hazard-prone residential communities. The residents are not new to the hazards in their area; with Bucana having an average of 40 years in the respondents? years of stay data. Based on the analysis of data, Bucana was the most vulnerable among the study areas; with five (5) climate-related hazards in the area. The Capacity and Resilience of the communities were also measured and analyzed; addressing the coping and adaptation techniques used by the residents. Therefore, the relationship between Vulnerability, Capacity, and Resilience is fundamental in the development of design strategies for an adaptive housing design against climate change.